2014
DOI: 10.1039/c4sm00596a
|View full text |Cite|
|
Sign up to set email alerts
|

Breaking of the Bancroft rule for multiple emulsions stabilized by a single stimulable polymer

Abstract: We investigated emulsions of water and toluene stabilized by (co)polymers consisting of styrene (S) and 2-(dimethylamino)ethyl methacrylate (DMAEMA) monomer units with different compositions and structures such as a PDMAEMA homopolymer, a P(S-co-DMAEMA) random copolymer and various PS-b-PDMAEMA and PS-b-(S-co-DMAEMA) block copolymers. The model system is used to study the fundamental conditions under which the different kinds of polymer-stabilized emulsions (direct oil in water, inverse water in oil and multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 54 publications
3
33
0
Order By: Relevance
“…The fact that no multiple emulsions are formed with this system is consistent with the architecture of the polymer used in this study since previous results on other systems 25 have shown that no multiple emulsions are formed when the hydrophilic block of the copolymer is purely constituted of DMAEMA. Here, it is also found out that no pH-driven phase inversion takes place for this system at I = 0 mol.L -1 .…”
Section: (A) (B') (C') (D') (E') (F') (G') (H') (I')supporting
confidence: 72%
See 3 more Smart Citations
“…The fact that no multiple emulsions are formed with this system is consistent with the architecture of the polymer used in this study since previous results on other systems 25 have shown that no multiple emulsions are formed when the hydrophilic block of the copolymer is purely constituted of DMAEMA. Here, it is also found out that no pH-driven phase inversion takes place for this system at I = 0 mol.L -1 .…”
Section: (A) (B') (C') (D') (E') (F') (G') (H') (I')supporting
confidence: 72%
“…Emulsions stabilized with these copolymers were stable for several months but were also stimuli-responsive with a capacity of encapsulation tuned by pH or temperature 17,25 . The latter study showed that the architecture of the polymer is important for the stabilization of multiple emulsions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, true liquid/liquid measurements are now emerging owing due to gain performances of the present reflectometers compared to those operating thirty years ago. For instance, in reference [15], water-toluene interface was probed in a cell specifically designed for the purpose. The beam crossed a sapphire before travelling through several hundreds of microns of water before hitting the toluene interface.…”
Section: The Different Possible Geometries Of Measurementsmentioning
confidence: 99%